PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN GENDER DIVERSITY TERHADAP MANAJEMEN LABA - Yoga Putra Meyditiya; Sonya Ajeng Wahyu Nastiti; Imsa Indri Astuti (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The purpose of this study was to determine corporate governance, profitability, leverage, company size and gender diversity on earnings management in automotive sector companies listed on the Indonesia Stock Exchange for the period 2020-203. This study uses secondary data, namely the annual financial statements of automotive sector companies listed on the IDX for the period 2020-2023. The sampling criteria used purposive sampling method and resulted in a research sample of 36 data. This research is quantitative research. The analysis in this study uses multiple linear regression analysis method using SPSS (Statistical Production Service Solution) software version 25. The results of this study indicate that the variables of the Independent Board of Commissioners and Leverage partially affect earnings management. Meanwhile, Institutional Ownership, ROA, Company Size, and Gender Diversity have no partial effect on earnings management. Meanwhile, the variables of the Independent Board of Commissioners, Institutional Ownership, ROA, Leverage, Company Size, and Gender Diversity simultaneously affect earnings management.